Residual stress analysis and finite element modelling of repair-welded titanium sheets - Salerno, G.; Bennett, C.J.; Sun, W.; Becker, A.A. (Springer, 2017)
An innovative FE modelling approach has been tested to investigate the effects of weld repair thin sheets of titanium alloy, taking into account pre-existing stress field in the components. In the case study analysed, the residual stress fields due to the original welds are introduced by means of a preliminary sequentially-coupled thermo-mechanical analysis and considered as pre-existing stress in the sheets for the subsequent weld simulation. Comparisons are presented between residual stress predictions and experimental measurements available from the literature with the aim of validating the numerical procedure. As a destructive sectioning technique was used in the reference experimental measurements, an investigation is also presented on the use of the element deactivation strategy when adopted to simulate material removal. Although the numerical tool is an approximate approach to simulate the actual material removal, the strategy appears to compute a physical strain relaxation and stress redistribution in the remaining part of the component. The weld repair modelling strategy and the element deactivation tool adopted to simulate the residual stress measurement technique are shown to predict residual stress trends which are very well correlated with experimental findings from the literature.